Cross-hole electrical resistivity tomography as an aid in monitoring marine gas hydrate reservoirs for gas recovery: an experimental simulation study. Issue 1 (18th November 2022) - Liu, Yang; Zou, Changchun; Chen, Qiang; Zhao, Jinhuan; Li, Yanlong; Sun, Jianye; Liu, Changling; Peng, Cheng; Wu, Caowei
SUMMARY: The in situ reservoir status monitoring plays a critical role in natural gas hydrate resource production. Considering the complexity of the field environment, a simulation framework for monitoring gas hydrates with cross-hole electrical resistivity tomography (CHERT) was developed to monitor the hydrate distribution during hydrate formation and dissociation. The simulation study comprised both numerical and physical experiments. The optimal CHERT array was designed through a numerical experiment. The effect of applying CHERT was verified through a physical experiment (a high-resistivity medium and hydrate formation experiment). The results show that improper electrode layouts will lead to varying degrees of low amplitude and blur boundary. An optimal CHERT array of a 100-mm electrode rod spacing, 8-mm electrode ring spacing and 48 electrode rings was obtained. The inversion results obtained using this CHERT array scheme can easily distinguish the distribution of high-resistivity targets and yield satisfactory results in hydrate formation experiments. These findings guarantee data processing and interpretation for applying CHERT in gas hydrate experiments and fields.